Sociological approach of differential care in Down syndrome screening based on maternal place of birth. (20th October 2021) - Sauvegrain, P; Cognet, M; Azria, E
Abstract: Background: In recent years, differential care in the field of perinatal medicine between women from sub-Saharan Africa and natives, such as suboptimal screening of preeclampsia or more frequent use of C-section have been identified. The objective of this study, in connection to the other parts of the BiP project, was to document differential care between these categories in regard with information on Down syndrome screening. Methods: Prospective qualitative study by audio-recording and/or observation of prenatal visits, ultrasound examinations and genetic screening consultation, and semistructured explicitation interviews with care providers was conducted in 3 maternity units in Paris area. Two midwives and 2 obstetricians in each unit were included, such as their patients who consent to participate. The content of the consultations was classified thematically, and the interviews were analyzed using the grounded theory framework. Results: 47 prenatal visits, 19 ultrasound examinations and 11 genetic screening consultations have been audio-registred and/or observed. Participation rate was 85% for the women. Semi-structured explicitation interviews were conducted among 11/12 care providers. Despite a probable inclusion bias (participants were informed of the purpose of the research and were volunteers), differences in care provider - patient interactions according to women's place of birth have been identified. A tendency to speak more loudly with women with lower French proficiency was noted and less detailed information on the screening strategy and on Down syndrome was provided. The use of an interpreter was very rare in situations of language barrier, challenging the information quality on Down syndrome screening. Conclusions: Beside showing differences in care provider - patient interaction according to women's place of birth, this study provides an opportunity to discuss the benefits and limitations of qualitative approaches to the study of differential care.